2020
DOI: 10.1142/s0218348x20501145
|View full text |Cite
|
Sign up to set email alerts
|

Complexity-Based Classification of the Coronavirus Disease (Covid-19)

Abstract: COVID-19 is a pandemic disease, which massively affected human lives in more than 200 countries. Caused by the coronavirus SARS-CoV-2, this acute respiratory illness affects the human lungs and can easily spread from person to person. Since the disease heavily affects human lungs, analyzing the X-ray images of the lungs may prove to be a powerful tool for disease investigation. In this research, we use the information contained within the complex structures of X-ray images between the cases of COVID-19 and oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…This infectious disease have severely hit China, Europe, United States, Brazil and South-East Asia (Johns Hopkins Coronavirus Resource Center, Johns Hopkins Coronavirus Resource Center, 2020; WHO, 2020a). More than 200 countries' communities have endured the poignant impact of COVID-19 (Namazi & Kulish, 2020). The COVID-19 registered global cases were 35,079,152 as of the 4 October 2020 (Johns Hopkins Coronavirus Resource Center, Johns Hopkins Coronavirus Resource Center, 2020), whereas 1,036,111 global deaths were also recorded due to this pandemic (Johns Hopkins Coronavirus Resource Center, Johns Hopkins Coronavirus Resource Center, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This infectious disease have severely hit China, Europe, United States, Brazil and South-East Asia (Johns Hopkins Coronavirus Resource Center, Johns Hopkins Coronavirus Resource Center, 2020; WHO, 2020a). More than 200 countries' communities have endured the poignant impact of COVID-19 (Namazi & Kulish, 2020). The COVID-19 registered global cases were 35,079,152 as of the 4 October 2020 (Johns Hopkins Coronavirus Resource Center, Johns Hopkins Coronavirus Resource Center, 2020), whereas 1,036,111 global deaths were also recorded due to this pandemic (Johns Hopkins Coronavirus Resource Center, Johns Hopkins Coronavirus Resource Center, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The term "Coronophobia" has been shifted from the epicenter of China to Europe, United States, Brazil, and the South Asian region [6]. More than 200 countries have already been affected [7]. The frontline health sector has been paralyzed in many countries due to the pandemic [4,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…While the use of fractal dimension for x-ray image analysis has focused on the study of bone tissue [ 42 , 43 ] examples of its use can be found in a wide variety of clinical settings, as brain structures analysis [ 44 ] or vascular patterns studies [ 45 ]. However, its use in the pneumonia detection in X-ray has been so far limited [ 46 ].…”
Section: Introductionmentioning
confidence: 99%